2017
DOI: 10.1371/journal.pone.0171457
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebellar gray matter volume in head chefs

Abstract: ObjectiveChefs exert expert motor and cognitive performances on a daily basis. Neuroimaging has clearly shown that that long-term skill learning (i.e., athletes, musicians, chess player or sommeliers) induces plastic changes in the brain thus enabling tasks to be performed faster and more accurately. How a chef's expertise is embodied in a specific neural network has never been investigated.MethodsEleven Italian head chefs with long-term brigade management expertise and 11 demographically-/ psychologically- ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Hence, in a condition characterized by long-lasting impairment of distal muscle strength, manual dexterity, and walking ability ( 3 ), as well as by reduced afferent and efferent stimuli to and from the CNS, the observed increase of anterior cerebellar regional volume might reflect mechanisms of structural plasticity ( 35 ) aimed at compensating peripheral nerve deficit and enduring brain deafferentation in CMT1A patients. Indeed, similar increases of cerebellar regional GM volume have been demonstrated in healthy individuals professionally subjected to the persistent solicitation of specific motor or cognitive abilities ( 36 , 37 ), while brain structural and functional plasticity phenomena have also been reported in other peripheral neuropathies ( 11 , 38 ). In accordance with this speculation, in our study we found an inverse correlation between the increase of GM volume in the right anterior cerebellum and the CMAP obtained from ulnar motor nerve, considered as a measure of distal arm axonal damage ( 15 ).…”
Section: Discussionsupporting
confidence: 54%
“…Hence, in a condition characterized by long-lasting impairment of distal muscle strength, manual dexterity, and walking ability ( 3 ), as well as by reduced afferent and efferent stimuli to and from the CNS, the observed increase of anterior cerebellar regional volume might reflect mechanisms of structural plasticity ( 35 ) aimed at compensating peripheral nerve deficit and enduring brain deafferentation in CMT1A patients. Indeed, similar increases of cerebellar regional GM volume have been demonstrated in healthy individuals professionally subjected to the persistent solicitation of specific motor or cognitive abilities ( 36 , 37 ), while brain structural and functional plasticity phenomena have also been reported in other peripheral neuropathies ( 11 , 38 ). In accordance with this speculation, in our study we found an inverse correlation between the increase of GM volume in the right anterior cerebellum and the CMAP obtained from ulnar motor nerve, considered as a measure of distal arm axonal damage ( 15 ).…”
Section: Discussionsupporting
confidence: 54%
“…In this study, the greater cerebellum GMV was specifically located in the lobules IV-V of the cerebellum and the IV-V vermian lobules in the anterior cerebellum lobe. These areas represent the arms, hands, and feet (Buckner, Krienen, Castellanos, Diaz, & Yeo, 2011;Manni & Petrosini, 2004) and are especially involved in motor execution, synchronization, coordination, control, and prediction (Cerasa et al, 2017;Koziol et al, 2014;Stoodley & Schmahmann, 2010;Wenzel, Taubert, Ragert, Krug, & Villringer, 2014). In addition, the GMV expansion in the athlete group extended to the bilateral lingual gyrus, PCC, and PCUN, which played important roles in visual attention.…”
Section: Gmv Differences Between Athletes and Controlsmentioning
confidence: 99%
“…Plenty of cross-sectional imaging studies have demonstrated structural brain differences between experts in music, sport, and video games and nonexperts and showed that experts had more gray matter volume (GMV) in certain brain regions. [11][12][13][14][15][16][17] However, deliberate practice is necessary but not sufficient to account for individual differences in experts and novices. [18][19][20] One of the criticisms of cross-sectional studies as providing the evidence for practice-dependent brain changes is that preexisting differences in brain organization could explain some of the differences we observe between experts and nonexperts.…”
Section: Introductionmentioning
confidence: 99%